Towards A Transcultural Formation: A Postcolonial Reading Of Isabel Allende’s Selected Texts - Behabadi, Tahereh Zamani (2013)
This dissertation focuses on three contemporary self-representational novels by the Latin American author, Isabel Allende. From a dual, postcolonial and transcultural perspective, this work analyzes the thematic structures and mode of writing used by the author to create or re-create a zone for silenced and marginalized groups to speak out. The stories are rooted in the South American continent‟s real socio-historical events, and the complexities and contradictions of the contemporary Latin American cultural context. Elaborating on certain postcolonial concepts, particularly the theories proposed by Homi Bhabha and Frantz Ortiz, the present dissertation identifies the process by which Allende makes opposing voices and methods of representation commingle to form an ideal hybridized model, both in characterization and in writing mode. In other words, the emergence of mestizo and magical realism are equally the results of a cultural syncretism. As transcultural phenomena, they share the feature of a negation of negotiability, since their negotiability is attained only after an introductory phase of negation. The present dissertation analyzes Allende‟s three novels, The House of the Spirits, Daughter of Fortune, and Zorro, and explores the mechanism by which the author disarms the dominant colonial discourse, through re-writing history from the viewpoint of the colonized and marginalized groups, and re-creating a new image of the self via her unique art of characterization.